Hubungan Antara Kecemasan Akademik dengan Self-Efficacy pada Mahasiswa yang sedang menyusun Skripsi di rumpun Ilmu Pendidikan FKIP Universitas Nusa Cendana - Lusi, Anton; Nalle, Andriani Paulin; Saba, Khetye Romelya (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2023)
Academic anxiety is one of the psychological problems that can be caused by low self-efficacy. This research aims to determine the description of academic anxiety in students who are preparing a thesis, a description of self-efficacy in students who are preparing a thesis and the relationship between academic anxiety and self-efficacy in students who are preparing a thesis in the Education Science group at the Faculty of Teacher Training and Education, Nusa Cendana University. The approach used in this research is quantitative with descriptive correlational research. This research was conducted in the clump of Education Sciences Faculty of Teacher Training and Education, University of Nusa Cendana Kupang with a population of 500 students. The sampling technique used was purposive sampling with a sample size of 100 students. Data collection techniques using academic anxiety scale and self-efficacy scale. The data analysis technique used is descriptive analysis and product moment correlation analysis. The results showed that academic anxiety in students who are preparing a thesis is dominant in the high category with 38 student respondents (38%), while self-efficacy in students who are preparing a thesis is dominant in the low category with 36 student respondents (36%). The results of the product moment correlation test show that there is a significant relationship between Academic Anxiety and Self-Efficacy as evidenced by the value of r count: -0.286 > r table -0.197 and significance < alpha probability which is 0.000 < 0.05. A significant negative relationship exists between academic anxiety and self-efficacy, meaning that the higher the academic anxiety experienced by students, the lower the self-efficacy when compiling a thesis, and vice versa, the lower the academic anxiety of students, the higher the self-efficacy of students when compiling a thesis.